PENGARUH MODEL REALISTIC MATHEMATICS EDUCATION BERBANTUAN MEDIA PANZAT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Ervida Eka Aurelya; Eka Zuliana; Fatikhatun Najikhah (De Fermat : Jurnal Pendidikan Matematika, 2026)
This research is motivated by the low mathematical problem-solving ability of students caused by the lack of learning activities and teacher-centered learning. This study aims to determine the effect of the Realistic Mathematics Education (RME) learning model assisted by PANZAT media on the mathematical problem-solving ability of elementary school students and examine the role of learning activities in supporting these abilities. This study uses a quantitative approach with a pre-experimental design of one group pretest-posttest. The subjects of the study were 42 second-grade students of SD Negeri 5 Ngabul. Data collection techniques used interviews, observations, and tests, while data analysis included normality tests, paired sample t-tests, and simple regression tests. The results showed that there was a significant difference between the pretest and posttest scores with a significance value of 0.000 <0.05. In addition, learning activities had a positive and significant effect on mathematical problem-solving ability with a correlation coefficient of 0.788 and a determination coefficient of 0.622. Thus, RME learning assisted by PANZAT media has a positive effect on students' learning activities and mathematical problem-solving abilities